Feminist Community-led Perspectives on Disaster Adaptations: Stories from Wetland Local Women Communities in Bangladesh - Hurlbert, Margot; Kairy, Barsha; Datta, Ranjan (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
This paper offers an in-depth exploration of the critical role played by women within vulnerable wetland communities in Bangladesh, particularly in the context of disaster adaptations. As climate change-induced disasters become increasingly prevalent, it is essential to recognize women’s agency, knowledge, and resilience within these communities, and between minority Hindu and majority Muslim women. Employing a feminist framework, this research delves into the nuanced dynamics of gender, faith, and community-based disaster adaptation strategies. Through narratives and stories from local women, the paper unveils the innovative and adaptive approaches often overlooked in conventional disaster management practices, the heightened agency of majority Muslim women and their “witnessing” of the suffering of the minority Hindu women. It highlights the intersectionality of gender, faith, poverty, and environmental vulnerability, shedding light on the unique challenges faced by women in wetland areas, especially vulnerable Indigenous and Hindu minority women. The findings of this paper underscore the need for more inclusive, gender-responsive disaster policies and programs, and call for a shift away from top-down approaches to more participatory, community-led solutions. By amplifying the voices and experiences of local women in Bangladesh, this paper contributes to a broader discourse on sustainable disaster adaptation strategies, ultimately striving for greater equity and resilience in the face of climate-related challenges.